Employee tenure and staff performance: The case of a social enterprise - Cécile Godfroid; Naome Otiti; Roy Mersland (Journal of Business Research, 2022)
The literature on social enterprises has largely examined tradeoffs at the organizational level. In this study, we examine tradeoffs at the employee level. By analyzing the case of an Ecuadorian microfinance institution, we show that the tenure of social enterprise employees affects individual social and financial performance differently: the relationship between tenure and social performance is positive, whereas the relationship between tenure and financial performance is an inverted U-shape. Furthermore, our results suggest that social enterprise employees with the longest tenure are the least inclined to experience tradeoff tensions.
Keywords: 650